Arabic Version of Learning Organization Survey Short-Form: Hospital Pharmacy Settings. (June 2021) - Abdallah, Wael; Johnson, Craig; Nitzl, Christian; Mohammed, Mohammed Amin
Objective: The objective of this study was to assess the psychometric properties of a translated Arabic version of the Learning Organization Survey (LOS-27) and to use this to evaluate staff perceptions about the organizational learning process in Kuwaiti hospital pharmacies.Setting: This study adopted a cross-sectional survey of the pharmacy employees in 6 hospital pharmacies in Kuwait.Results: The results indicated that the internal consistency of all composites was more than 0.7, except for one. All item loadings for the construct measurements were above 0.7. The standardized root mean square residual (SRMR) score showed a good fit with a value of 0.08. The intercorrelation among composites ranged from 0.34 to 0.68.Conclusions: The results indicate that the Arabic translation of the LOS-27 questionnaire has adequate levels of reliability and validity in comparison with the original US survey results. The overall average positive rate of composites was 64%. Therefore, the findings suggest that the hospital pharmacy staff surveyed in Kuwait were moderately positive in their perceptions about organizational learning in their organizations.